(untitled) (Global Journal of Science Frontier Research, 2023)
This manuscript provides a comprehensive review of the Taenia genus encompassing 44 reported species and their impact on domestic and wild animals as well as humans The review focuses on 10 important Taenia species and covers various aspects including their description life cycle epidemiology clinical signs of taeniosis and cysticercosis diagnosis treatment control and prevention While humans primarily serve as the definitive hosts for Taenia asiatica T saginata and T solium they can also become intermediate accidental hosts for larval forms metacestodes of Taenia crassiceps T multiceps T serialis T solium and Taeniaeformis These larval forms can cause a range of pathologies in the brain liver muscle eye and subcutaneous tissue Human cysticercosis particularly from T solium results in significant hospital treatment costs loss of productivity and even death